Cascading a New Knowledge: The Implementation of Reference Management Software in The Academic Writing Class - Renata Kenanga Rinda; Nodistya Septian Indrastana; Rizqi Febrian Pramudita; Wahyu Indah Mala Rohmana; Puput Jianggimahastu Larastika Suryanto (Journal of English in Academic and Professional Communication, 2022)
College students should meet numerous requirements to produce a well-written academic paper. One of those requirements is constructing correct references. Nonetheless, based on the phenomenon spotted in the author’s academic writing class, arranging references manually is not an effortless task. Time-consuming and style memorizing are the two main obstacles faced by the students. To answer the preceding problems, the author, the teacher in charge in class, proposed a solution by implementing EndNote as reference management software. It enables students to write references automatically. Seventy students were involved as the participants while EndNote was administered. To cascade the knowledge of the mechanism of implementing EndNote, this paper aimed to describe the steps involved. Video recording and checklist form were utilized as research instruments. The results revealed four steps of implementing EndNote used by the teacher. They are planning, implementation, observation, and reflection. By explaining those steps, it is expected that the mechanism of implementing EndNote can be explained and adapted by other teachers and students facing the same problems.